1997
DOI: 10.1099/0022-1317-78-10-2489
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human immunodeficiency virus type 1 particle formation by alterations of defined amino acids within the C terminus of the capsid protein.

Abstract: In previous studies, we demonstrated that the substitution of amino acid triplets for alanines in the carboxy-terminal portion (amino acids 341-352 : ATL EEM MTA CQC) of the capsid protein domain (p24) of human immunodeficiency virus type 1 (HIV-1) partly led to an inhibitory effect on the capacity to form virus-like particles (VLPs). In these experiments, the uncleaved Pr55 gag precursor protein was expressed by recombinant vaccinia viruses. We have now investigated the effects of these mutations with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In support of this idea, removal of RNA by RNase digestion disrupts formation of Gag complexes (32). The second domain encompasses the C-terminal domain of CA (11,31,52,61,63,66) and the adjacent spacer peptide, p2 (1,30,34,44,62). In a structural view, p2 represents an extension of a putative ␣-helix from the C terminus of CA (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this idea, removal of RNA by RNase digestion disrupts formation of Gag complexes (32). The second domain encompasses the C-terminal domain of CA (11,31,52,61,63,66) and the adjacent spacer peptide, p2 (1,30,34,44,62). In a structural view, p2 represents an extension of a putative ␣-helix from the C terminus of CA (1).…”
mentioning
confidence: 99%
“…In addition to these three functional domains, the C-terminal domain (CTD) of CA (CA amino acids 150 to 231) is also indispensable for virus particle formation (11,31,52,61,63,66). Within this domain exists a major homology region (MHR) that is highly conserved among retroviral Gag proteins.…”
mentioning
confidence: 99%
“…Structural studies and protein-protein interaction analyses have demonstrated that CA and SP1 likely contribute to Gag multimerization by facilitating direct interactions between Gag molecules (24, 29, 31, 33, 59-61, 67, 96). Mutations and deletions in the C-terminal domain of CA (12,21,42,50,56,58,76,82,87,88,90) and SP1 (1,45,49,93) cause defects in virus particle production, indicating that the Gag-Gag interaction mediated by this region is physiologically important for virus assembly. Unlike CA and SP1, NC is thought to promote Gag multimerization primarily through interaction with RNA.…”
mentioning
confidence: 99%
“…Bacterially expressed CA has been shown to assemble in vitro (10,20,51), and the C-terminal domain of CA dimerizes in the crystal structure in the absence of other domains (16). Mutations affecting the C-terminal domain of HIV-1 CA have also been shown to disrupt virus assembly (8,26,45,50,54,59). In contrast, mutations in the N-terminal domain of CA generally do not disrupt virus assembly but rather perturb proper virion maturation (45,52).…”
mentioning
confidence: 99%